Circulating microRNAs as potential biomarkers for unstable angina - Liu, Jun (Int J Clin Exp Pathol, 2017)
Background: Chest pain is a typical presentation in the emergency department (ED), often due to acute coronary syndrome. Accurate and fast identification is crucial. The diagnosis and proper treatment of unstable angina (UA) can reduce the chance of acute myocardial infarction, and reduce high mortality and morbidity rates. However there is a lack of reliable and valid biomarkers in the diagnosis of UA. This study investigated the usefulness of circulating microRNAs (miRNAs) for differentiating UA from non-ischemic chest pain (NICP) in the ED. Methods The expressions of circulating miRNAs in patients with UA were evaluated relative to individuals with NICP (control subjects). Circulating miR-21, miR-25, miR-92a, miR-106b, miR-126* and miR-451 levels were measured in 98 patients with UA and 95 control subjects in the ED. To investigate the underlying functions of miRNAs in UA, bioinformatic analysis of validated miRNAs was conducted. Results: Circulating miRNAs were upregulated in UA compared with the control group. The combination of the modified HEART score (m-HS) and miR-25 (AUC 0.901, NRI 0.096) could better distinguish UA than m-HS alone. Bioinformatic analysis indicated that miRNAs may take part in platelet activation, cGMP-PKG signaling pathways etc. Conclusion: The circulating levels of miRNAs (miR-21, miR-25, miR-106b, miR-126*) are significantly higher in UA patients compared with patients with NICP, and the addition of the m-HS that combined ECG, age, risk factors and troponin is useful to detect or rule out UA. The associated signaling pathways are involved in the pathogenesis of vulnerable plaque.